PENYUSUNAN PANDUAN INFORMASI DAYA TARIK WISATA DAN PROMOSI MEDIA SOSIAL PURI AGUNG DENPASAR - Rahyuda, I.; Kesumadewi, P.D.; Suwena, I.K.; Arismayanti, N.K. (Buletin Udayana Mengabdi; Vol 22 No 3 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i03.p03, 2023)
The existence of cultural heritage is increasingly being pushed aside due to modernization. In developing a city tour for Denpasar City, the information about this tourist attraction is not yet optimal. Information and promotion of tourist attractions is very important to attract tourists and visiting tourists. The limited information available and accessible to tourists certainly hinders the growth of tourism in an area. In particular, castle tourism requires a touch of innovation in tourism products in the midst of intense competition and trends in contemporary tourism products. This community service activity was carried out in Dangin Puri Kaja Village, North Denpasar District, Denpasar City, Bali with the aim of exploring and compiling information guides for castle tourist attractions and utilizing social media for the promotion of tourist attractions. The community service activity program carried out at Puri Agung Denpasar has achievement targets in the form of: an increase in digital promotion on an ongoing basis; there is a guide for the younger generation and visiting tourists; Denpasar City tourism is getting more vibrant through the development of castle tourism; social media promotion is complemented by tutorials on managing Instagram and Facebook accounts. This community service activity is expected to have a positive impact by increasing the recognition of Puri Agung Denpasar and increasing the income of the surrounding community from the increasing number of tourist visits. Keywords: travel guide, tourist attraction, promotion, social media, palace tourism, Puri Agung Denpasar.